PENGARUH BRAND IMAGE, BRAND TRUST, DAN KEPUASAN PELANGGAN TERHADAP BRAND LOYALTY PRODUK FACETOLOGY PADA TIKTOK SHOP DI KOTA BATAM - Kellie Natalie; Hikmah Hikmah (LPPM Universitas Putera Batam, 2026)
The rapid growth of social commerce, particularly on TikTok Shop, has created a dynamic yet competitive environment for emerging skincare brands like Facetology. This study investigates the influence of brand image, brand trust, and customer satisfaction on brand loyalty toward Facetology products among consumers in Batam City. Employing a quantitative descriptive-explanatory design, data were collected from 100 respondents using purposive sampling and analyzed using multiple linear regression. The results of the partial analysis (t-test) demonstrate that brand image, brand trust, and customer satisfaction each have a positive and significant impact on brand loyalty, with customer satisfaction emerging as the most dominant predictor. Furthermore, the simultaneous test (f-test) confirms that these three variables collectively influence brand loyalty, as reflected by an adjusted r-square value of 0.851. This indicates that 85.1% of the variance in brand loyalty is explained by these determinants, while external factors account for the remainder. These findings suggest that to sustain long-term loyalty within the social commerce ecosystem, brands must prioritize consistent product performance and packaging quality to foster high levels of trust and satisfaction.